Zosteriform speckled lentiginous nevus with bilateral segmental neurofibromatosis: A rare association - Bhagyashree B Supekar; Vaishali H Wankhade; Apoorva D Chopkar; Rajesh P Singh; Dharitri Bhat (Wolters Kluwer Medknow Publications, 2021)
Bilateral segmental neurofibromatosis is a nonfamilial variant of neurofibromatosis without any systemic involvement. Speckled lentiginous nevus (SLN) is a pigmented, light brown to tan patch of varied diameter, speckled with smaller, darker colored macules or papules. SLN has been reported in association with bilateral nevus of Ito, blue nevus, centrofacial lentiginosis, and nevus sebaceous. Its association with bilateral segmental neurofibromatosis has been rarely reported in the literature. We report a rare co-existence of zosteriform nevus spilus with bilateral segmental neurofibromatosis, diagnosed on the basis of clinico-dermoscopic-histopathological features, in a 25-year-old female.